2019
DOI: 10.3389/fpsyg.2019.00079
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How Accountability Affects the Medical Decisions We Make for Other People

Abstract: In the event that a patient has lost their decision-making capacity due to illness or injury, a surrogate is often appointed to do so on their behalf. Research has shown that people take less risk when making treatment decisions for other people than they do for themselves. This has been discussed as surrogates employing greater caution for others given the accountability they are faced with. We tested the prediction that making accountability salient reduces risk-taking for others relative to the self by mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…With consistent results from two studies, our work reveals a significant moderating role of intrinsic/extrinsic motivation in individuals’ risk-taking orientations in response to online review performance, and this effect appears immune to the size of dining parties. Although studies have suggested that making purchase decisions for others tends to undermine one’s decision autonomy, which leads to risk-averse choices due to a greater level of perceived accountability and anticipated blame and negative outcomes (Aaker & Lee, 2001; Batteux et al, 2019; Wu & Lee, 2016), our findings have underscored the importance of dining motivation in driving individuals’ risk tolerance in restaurant decision making regardless of the dining group sizes. As indicated in research released by OpenTable, dining occasions (e.g., purely eating out, a business meal, or a date night) reflect diners’ consumption goals and motivations, which informs diners’ behavior and what they want from visiting a restaurant (Hon, 2015).…”
Section: Discussionmentioning
confidence: 54%
“…With consistent results from two studies, our work reveals a significant moderating role of intrinsic/extrinsic motivation in individuals’ risk-taking orientations in response to online review performance, and this effect appears immune to the size of dining parties. Although studies have suggested that making purchase decisions for others tends to undermine one’s decision autonomy, which leads to risk-averse choices due to a greater level of perceived accountability and anticipated blame and negative outcomes (Aaker & Lee, 2001; Batteux et al, 2019; Wu & Lee, 2016), our findings have underscored the importance of dining motivation in driving individuals’ risk tolerance in restaurant decision making regardless of the dining group sizes. As indicated in research released by OpenTable, dining occasions (e.g., purely eating out, a business meal, or a date night) reflect diners’ consumption goals and motivations, which informs diners’ behavior and what they want from visiting a restaurant (Hon, 2015).…”
Section: Discussionmentioning
confidence: 54%
“…In our study, although most surgeons' would treat their patients' fingertip injury similarly to how they would treat their own fingertip injuries, several studies have demonstrated that people behave differently when they have are faced with a decision they have to make for themselves versus for another person. 24,[27][28][29][30] Surgeons may have felt more comfortable about the choice of treatment when choosing for themselves, given that they have more circumstantial information about themselves than they do about patients. Fifth, we did not examine culture and religious background which may play a role in deciding on treatment methods, especially in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, making decisions for others involves deciding directly for other people. In this case, fewer risks are assumed than when making decisions for oneself, both in financial matters (Eriksen et al, 2020), and in healthcare (Batteux et al, 2019a). In turn, regarding the scenario in which the decision is to be made (loss or gain), fewer risks are assumed when we make decisions for other people in scenarios in which there is a probability of loss, even though they may be accompanied by gains (Batteux et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%